V.S. Naipaul : critical essays [volume - III] - Ray, Mohit K. (New Delhi : Atlantic, 2002)
Contributed articles.
Includes bibliographical references.
DELL
Keywords: Naipaul, V. S. -- 1932- -- Criticism and interpretation